Revisit Bloom’s Taxonomy: A reflection of education in a digital era - Farani, Rizki (Journal of English Language and Pedagogy, 2022)
Bloom’s taxonomy has been used in the education field since 1956. It promotes a higher form of thinking in education. However, the shift from traditional classroom interaction to technology-based education, such as e-learning, blended learning, and distance learning, changes the paradigm on how educators design learning instruction. This article presents a general description of Bloom’s taxonomy application in the digital era based on some literature reviews. The articles were selected purposively among open-access journals only in two reputable international journals: (1) Computer and Education and (2) Cogent Education. The journals were selected due to their publication mostly related to Bloom’s taxonomy in the education field. The review covers two aspects: (1) the identification of Bloom’s taxonomy applications and (2) the modification of Bloom’s taxonomy to promote thinking skills. The analysis presents information on how educators modify Bloom’s taxonomy to deliver content through technology-based learning. The results show that: (a) there is limited access to identify Bloom’s Taxonomy studies; (b) there is limited open access to literature reviews on Bloom’s Taxonomy in the education field; (c) modification of Bloom’s Taxonomy in the digital era position technology as a tool to facilitate students’ learning, and (d) most learning only builds students’ cognitive skills. There is still a limited exploration of affective and psychomotor domains. As a further recommendation for future research, there is a demand to provide more open-access journals on how to use technology to support affective and psychomotor domains.